668 Recurrent concussions in United States high school athletes. (1st September 2016) - Currie, Dustin W; Pierpoint, Lauren A; Kerr, Zachary Y; Comstock, R Dawn
Abstract : Background: An estimated 1.6–3.8 million sports-related concussions occur annually in the United States. Previous research has indicated risk of recurrent concussion is especially high within 10 days after initial concussion. Recurrent concussions have been associated with negative long-term outcomes. This study compares severity of initial and recurrent concussions. Methods: Recurrent concussions within athletes in sport seasons were identified in the High School RIO database using a combination of factors including either athlete IDs, or combinations of demographic and sports-related variables, depending on available data. We calculated days between concussions, and paired analyses were completed comparing initial and recurrent concussion within athletes on symptomatology, symptom resolution and return to play time. Results: Concussion pairs were identified in 176 athletes. Median time between initial and recurrent concussions was 21 days (IQR:10–43 days). The only significant symptom difference between initial and recurrent concussion was loss of consciousness, which occurred more frequently in recurrent concussions (6.8% vs. 1.3%, p = 0.04). There was no significant difference in number of symptoms (p = 0.84) or symptom resolution time (p = 0.74). Recurrent concussions were much more likely to result in longer time loss from sport participation (p < 0.0001), with 27.6% of recurrent concussions being season-ending. Conclusions: We did not find evidence of significant differences between initial and recurrent concussions on measures of injury severity, however clinicians and athletes are treating these concussions differently in return to play clinical decision-making. Our study found a longer average amount of time between initial and recurrent concussions than previously reported, possibly due to change in concussion management guidelines. More research needs to be done comparing initial and recurrent concussions with a clearer mechanism to link injuries within athletes.